Editor's Note = Note du directeur [19, Spring 1987] - Kealey, Gregory S. (Labour / Le Travail, 1987)
Provides an overview of the current issue as the journal celebrates its 10th anniversary. Appreciation is expressed for the longstanding relationship the journal had with the printing service, which has drawn to a close. Papers presented emphasize the current state of labour and working-class history, including issues of gender and ethnicity. The editor gratefully acknowledges arrivals and departures of editorial board members. A research assistant has updated the journal's index. Memorial University of Newfoundland is thanked for its generous institutional support of the journal.

Strikes in Canada, 1891-1950: I. Analysis - Cruikshank, Douglas; Kealey, Gregory S. (Labour / Le Travail, 1987)
This three-part report presents the results of a major research project underdertaken in the early 1980s. The project aimed to establish a new statistical time series for strikes in Canada. The final results of this work will appear in 1990 in volume three of the Historical Atlas of Canada which will contain a series of four plates on Canadian labour in the years 1891-1961. In this report we shall focus on the data concerning the years 1891-1950. An essay on method and sources is published here as Part II of this report and the data set is presented fully in Part III. In addition, we want to state at the outset that the more we work on this data, the more fully we agree with David Montgomery's assertion that "any attempt to formulate a positivistic 'natural history of strikes* is doomed to failure. Strikes can only be understood in the context of the changing totality of class conflicts, of which they are a part." –From authors' introduction

Strikes in Canada, 1891-1950: III. The Data - Cruikshank, Douglas; Kealey, Gregory S. (Labour / Le Travail, 1987)
This three-part report presents the results of a major research project underdertaken in the early 1980s. The project aimed to establish a new statistical time series for strikes in Canada. The final results of this work will appear in 1990 in volume three of the Historical Atlas of Canada which will contain a series of four plates on Canadian labour in the years 1891-1961. In this report we shall focus on the data concerning the years 1891-1950. An essay on method and sources is published here as Part II of this report and the data set is presented fully in Part III. In addition, we want to state at the outset that the more we work on this data, the more fully we agree with David Montgomery's assertion that "any attempt to formulate a positivistic 'natural history of strikes* is doomed to failure. Strikes can only be understood in the context of the changing totality of class conflicts, of which they are a part." –From authors' introduction

Strikes in Canada, 1891-1950: II. Methods and Sources - Cruikshank, Douglas; Kealey, Gregory S. (Labour / Le Travail, 1987)
This three-part report presents the results of a major research project underdertaken in the early 1980s. The project aimed to establish a new statistical time series for strikes in Canada. The final results of this work will appear in 1990 in volume three of the Historical Atlas of Canada which will contain a series of four plates on Canadian labour in the years 1891-1961. In this report we shall focus on the data concerning the years 1891-1950. An essay on method and sources is published here as Part II of this report and the data set is presented fully in Part III. In addition, we want to state at the outset that the more we work on this data, the more fully we agree with David Montgomery's assertion that "any attempt to formulate a positivistic 'natural history of strikes* is doomed to failure. Strikes can only be understood in the context of the changing totality of class conflicts, of which they are a part." –From authors' introduction

Book Notes [19, Spring 1987] - Kealey, Gregory S.; Palmer, Bryan D. (Labour / Le Travail, 1987)
The article briefly reviews "The Structure of the Canadian Capitalist Class," by Robert J. Brym, "Democratic Socialism: The Challenge of the Eighties and Beyond," edited by Donna Wilson, "Old Passions, New Visions: Social Movements and Political Activism in Quebec," by Marc Raboy, "Frank H. Underhill; Intellectual Provocateur," by R. Douglas Francis, "Emerging Identities: Selected Problems and Interpretations in Canadian History," edited by Paul W. Bennett and Cornelius J. Jaenen, "Tobacco and Slaves: The Development of Southern Cultures in the Chesapeake, I680-1800," by Allan Kulikoff, "Will Herberg: A Bio-Bibliography," by Harry J. Ausmus, "Disorderly Conduct: Visions of Gender in Victorian America," by Carrol Smith-Rosenberg, "The Collected Essays of Asa Briggs, Volume 1: Words, Numbers, Places, People and Volume Two: Images, Problems, Standpoints, Forecasts," by Asa Briggs, "The Irish in the Victorian City," by Roger Swift and Sheridan Gilley, "British Economic Growth during the Industrial Revolution," by N.F.R. Crafts, "Language, Gentler and Childhood," edited by Carolyn Steedman, Cathy Urwin, and Valerie Walkerdine, "British Trade Unionism Against the Trades Union Congress," by Gerald A. Dorfman, "Artisans, Peasants, and Proletarians, 1760-1860: Essays Presented to Gwyn Williams," by Clive Emsley and James Walvin,"Labor Migration in the Atlantic Economies: The European and North American Working Classes During the Period of Industrialization," edited by Dirk Hoerder, "The Peculiarities of German History: Bourgeois Society and Politics in Nineteenth-Century Germany," by David Blackbourn and Geoff Eley, "The Development of Capitalism in Northern Nigeria," by Robert Shenton, "Capitalism and Social Democracy," by Adam Przeworski, "Outsiders: A Study in Life and Letters," by Hans Mayer / reviews by Bryan D. Palmer – "Talkin' Union: Music Lore History," journal edited by Saul Schniderman, "Nature's Noblemen: The Fortunes of the independent Collier in Scotland and the American Midwest, 1855-1885," by John H.M. Laslett / reviews by Gregory S. Kealey.

Book Notes (20, Fall 1987] - Palmer, Bryan D.; Kealey, Gregory S. (Labour / Le Travail, 1987)
The article briefly reviews "1919: The Winnipeg General Strike," by Gerry Berkowski and Nolan Reilly,"The Writing of Canadian Histo ry: Aspects of English-Canadian Historical Writing since 1900," by Carl Berger, "A Conjunction of Interests: Bus iness, Politics, and Tariffs, 1825-1879," by Ben Forster, "Vancouver Past: Essays in Social History," edited by Robert A.J. McDonald and Jean Barman, "Quebec before Duplessis: The Political Career of Louis-Alexandre Taschereau," by Bernard L. Vigod, "Canada, What's Left?," edited by John Richards and Don Kerr,"'My Dear Legs': Letters to a Young Social Democrat," by Alex Macdonald, "The Knights in Fiction: Two Labor Novels of the 1880s," edited by Mary C. Grimes, "Uncertain Victory: Social Democracy and Progressivism in Europe an and American Thought, 1870-1920," by James T. Kloppenberg, "The Growth of Working Class Reformism in Mid-Victorian England," by Neville Kirk, "Proletarians and Protest: The Roots of Class Formation in an Industrializing World," edited by Michael Hanagan and Charles Stephenson, "Servants and Masters in Eighteenth-Century France: The Uses of Loyalty ," by Sarah C. Maza, "The German Revolution and the Debate on Soviet Power — Documents: 1918-1919, Preparing the Founding Congress," edited by John Riddell,"The Ties That Bind: Peasant Families in Medieval England," by Barbara A. Hanawalt, "Households and the World Economy," edited by Joan Smith, Immanuel Wallerstein, and Hans Dieter Evers, "Revolutionaries and Reformists: Communism and the Australian Labour Movement, 1920-1950," by Robin Gollan, "The Theory of Monopoly Capitalism: An Elaboration of Marxian Political Economy," by John Bellamy Foster, "An Introduction to Marxist Political Economy," by Bade Onimode, "Workplace Democracy: A Guide to Workplace Ownership, Participation, and Self-Management Experiments in the United States and Europe," by Daniel Zwerdling, "The Future of the Left," edited by James Curran, "Blue Chips," by Herbert A. Applebaum / reviews by Bryan D. Palmer – "Something in Common - An IWW Bibliography," compiled by Dione Miles, "Samuel Gompers: A Selected List of References About the Man and His Time," by David Myers / reviews by Gregory S. Kealey.